2016
DOI: 10.1111/1471-0528.14372
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, pre‐eclampsia, and preterm birth among pregnancies at high risk for pre‐eclampsia: an analysis of data from a low‐dose aspirin trial

Abstract: Vitamin D is inversely related to risk of pre-eclampsia and preterm birth at <35 weeks in high-risk pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Early observational studies suggested a consistent relationship between maternal circulating concentrations of 25(OH)D and preeclampsia ( 13 , 51 53 ), altered placental vascular pathology ( 54 ), cesarean section rates ( 55 ), glucose intolerance ( 56 ), adverse birth outcomes due to race and ethnicity ( 57 ), brain dysfunction ( 50 ) and respiratory dysfunction ( 38 ). Since 1980, studies have shown that maternal vitamin D deficiency is a variety of adverse health outcomes, which include abnormal fetal growth patterns (with the likelihood of alteration in growth associated with extreme deficiency) ( 58 ), adverse birth outcomes (such as preterm birth) ( 59 , 60 ), reproductive failure ( 61 65 ), and have further strengthened vitamin D's role as a contributing factor in the manifestation and progression of disease leading to preeclampsia ( 66 , 67 ). A recent meta-analysis of observational studies has found a positive relationship between maternal vitamin D deficiency and the risk of preterm birth ( 68 ).…”
Section: Vitamin D Deficiency During Pregnancy: Human Studiesmentioning
confidence: 99%
“…Early observational studies suggested a consistent relationship between maternal circulating concentrations of 25(OH)D and preeclampsia ( 13 , 51 53 ), altered placental vascular pathology ( 54 ), cesarean section rates ( 55 ), glucose intolerance ( 56 ), adverse birth outcomes due to race and ethnicity ( 57 ), brain dysfunction ( 50 ) and respiratory dysfunction ( 38 ). Since 1980, studies have shown that maternal vitamin D deficiency is a variety of adverse health outcomes, which include abnormal fetal growth patterns (with the likelihood of alteration in growth associated with extreme deficiency) ( 58 ), adverse birth outcomes (such as preterm birth) ( 59 , 60 ), reproductive failure ( 61 65 ), and have further strengthened vitamin D's role as a contributing factor in the manifestation and progression of disease leading to preeclampsia ( 66 , 67 ). A recent meta-analysis of observational studies has found a positive relationship between maternal vitamin D deficiency and the risk of preterm birth ( 68 ).…”
Section: Vitamin D Deficiency During Pregnancy: Human Studiesmentioning
confidence: 99%
“…Preeclampsia is a risk factor for premature birth whose only treatment is birth [36,37]. A large body of evidence indicates that increased inflammatory response is a feature of systemic vascular dysfunction in this disorder, although its cause is not completely known [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated an association between vitamin D deficiency and other conditions, independent from the direct role of vitamin D in calcium and bone metabolism. Vitamin D deficiency during pregnancy has been associated with increased risk of pre-eclampsia [57] and an increased risk of asthma [34] and type 1 diabetes [58] in the offspring of vitamin D deficient mothers, warranting further research to determine possible underlying mechanisms. Ensuring vitamin D adequacy through maternal oral supplementation of vitamin D 3 at a level of 80 µg (3200 IU) per day is safe and would prevent most forms of rickets as well as reducing incidence of some complications of pregnancy that are harmful to the mother and foetus.…”
Section: Discussionmentioning
confidence: 99%